2006
DOI: 10.1111/j.1600-0722.2006.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of stem cell factor and its receptor, c‐kit, in human oral mesenchymal cells

Abstract: Stem cell factor (SCF) is the pleiotropic ligand for the tyrosine kinase receptor, c-kit. Ligand and receptor are usually expressed in different cell types, and binding of SCF to c-kit promotes cell proliferation, differentiation, and recruitment of progenitor cells in various biologic systems. However, the localization of these two molecules in cells of the oral cavity has not been systematically examined. We investigated the expression of SCF and c-kit in human dental pulp (HDP) cells as well as in human gin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 30 publications
0
38
1
Order By: Relevance
“…Stem cells are generally defined as clonogenic cells capable of both self-renewal and multi-lineage differentiation. The stem cell factor, the pleiotropic ligand for the tyrosine kinase receptor (c-kit), has been demonstrated in human dental pulp by Western analysis (Gagari et al, 2006). Previous studies have shown that stem cells isolated from the pulp of adult human teeth and expanded in vitro showed an 9% positivity for STRO-1, an antibody that recognizes a cell surface antigen present on precursors of various stromal cell types including marrow fibroblasts, osteoblasts, chondrocytes, adipocytes, and smooth muscle cells isolated from human adult and fetal bone marrow (Simmons and Torok-Storb, 1991;Oyajobi et al, 1999;Dennis et al, 2000).…”
Section: Differentiation Capabilities Of Hdpcs In Vitromentioning
confidence: 99%
“…Stem cells are generally defined as clonogenic cells capable of both self-renewal and multi-lineage differentiation. The stem cell factor, the pleiotropic ligand for the tyrosine kinase receptor (c-kit), has been demonstrated in human dental pulp by Western analysis (Gagari et al, 2006). Previous studies have shown that stem cells isolated from the pulp of adult human teeth and expanded in vitro showed an 9% positivity for STRO-1, an antibody that recognizes a cell surface antigen present on precursors of various stromal cell types including marrow fibroblasts, osteoblasts, chondrocytes, adipocytes, and smooth muscle cells isolated from human adult and fetal bone marrow (Simmons and Torok-Storb, 1991;Oyajobi et al, 1999;Dennis et al, 2000).…”
Section: Differentiation Capabilities Of Hdpcs In Vitromentioning
confidence: 99%
“…CD117 has been reported to be expressed in adult / neonatal DPC (18,19) and PDLC (20). When stem cell factor (SCF) binds to CD117, cell proliferation, cell migration, angiogenesis and tissue remodeling can be induced.…”
Section: Resultsmentioning
confidence: 99%
“…Over-expression of SCF/c-Kit is associated with the inflammatory reaction, proliferation spread, and wound repair (Kalra et al, 2013). Expression of the SCF/cKit receptor and its ligand in epithelial tissues has been found to be associated with neoplastic transformation (Gagari et al, 2006). Therefore, SCF has a close relationship with allergic asthma, liver tissue fibrosis, small cell lung cancers, and so on (Choudhary et al, 2016).…”
Section: Discussionmentioning
confidence: 99%